تحليل القوائم المالية باستخدام نافذة تحليل مغلف البيانات - ديك, رولى; ياسين, بتول (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يحظى تحليل البيانات المالية باهتمام مستخدمي البيانات الداخليين أو الخارجيين، وذلك بسبب حاجتهم للحصول على معلومات مالية عن الشركة ومدى قوة مركزها المالي. وعلى الرغم من اعتبار تحليل النسب أحد أفضل وسائل تحليل البيانات المالية، إلا أن تفسيره غالباً ما يكون صعباً ومثيراً للجدل. حيث أن كل مجموعة من النسب ممكن أن تعطي بعدمالي واحد. وبالتالي يصبح من الصعب دمج نتائج مجموعات مختلفة من التحليلات المالية. لذلك ظهر أسلوب يكمّل تحليل النسب وهو تحليل مغلف البيانات الذي تم استخدامه في هذا البحث مع أسلوب النافذة وباستخدام نموذج عوائد الحجم المتغيرة المعروف ب BCC نسبة للباحثين Banker, Charnes and Cooper لتقييم كفاءة 19 شركة تابعة للمؤسسة العامة للصناعات الغذائية خلال الفترة من عام 2008-2010. ودراسة اتجاه تغيرات الأداء ومعرفة أي شركة أفضل من خلال ترتيبها من الشركة الأعلى كفاءة إلى الأقل كفاءة باستخدام نموذج Super- Efficiency. أظهرت نتائج الدراسة أن عدد الشركات الكفوءة هي 6 شركات وعدد الشركات غير الكفوءة هي 13 شركة. كما تبين أن شركة مياه بقين حصلت على أعلى كفاءة وشركة كونسروة الحسكة حصلت على أقل كفاءة. كما تبين التراجع الواضح في كفاءة جميع الشركات خلال فترة الدراسة. Internal and external data users are interested in financial data analysis, because of their need to obtain financial information about the company and to know the strength of its financial position. Although ratio analysis is always considered as one of the best financial statements analysis methods, but its interpretation is often difficult and controversial. Where each group of ratios can only show a single financial dimension, thus it may be difficult, when analyzing financial statements, tointe grate the results of different groups of financial analyses. So, an approach namely Data Envelopment Analysis, which is used in this research with Window approach by using variable returns of scale model, known as BCC related to researches Banker, Charnes and Coopers. In order to study the efficiency of the 19 sub-company of the General Establishment for food industries during the period 2008-2010. And also to study the direction of performance changes, in order to determine the best and the worst company through the company's efficiency using Super-Efficiency model. The study results showed that the number of efficient companies are six, and the number of inefficient companies are 13. Also showed that the Boken Water Company got the highest efficiency, and the company conserves Hasaka got less efficiency. All companies have less efficiency during the study period.